A case of Vogt-Koyanagi-Harada-like uveitis secondary to dabrafenib/trametinib therapy for advanced melanoma. Issue 1 (January 2022) - Brambati, Maria; Giuffrè, Chiara; Marchese, Alessandro; Bandello, Francesco; Modorati, Giulio Maria; Miserocchi, Elisabetta
We report a case of ocular drug toxicity consistent with bilateral Vogt-Koyanagi-Harada (VKH) like disease in a patient with cutaneous melanoma treated with Dabrafenib/Trametinib therapy. A 53-year-old man with a history of metastatic cutaneous melanoma, treated with Dabrafenib/Trametinib, developed a severe acute panuveitis with granulomatous anterior uveitis and multiple serous retinal detachments. The ocular inflammatory reaction was classified as a bilateral Vogt-Koyanagi-Harada disease. Intraocular inflammation resolved after discontinuation of chemotherapeutic agents and aggressive topical and systemic corticosteroid therapy. The present case outlines the importance of recognizing VKH-like syndrome as a possible consequence of therapy with dabrafenib and trametinib.